2017
DOI: 10.1373/jalm.2016.022582
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide-Nitroprusside Colorimetric Assay: A Rapid Colorimetric Screen for Urinary Cystine

Abstract: Background Cystinuria is an autosomal recessive disorder resulting in poor proximal tubule reabsorption of cystine in the nephron, increasing the risk of cystine stone formation. A fast, inexpensive assay to screen for urinary cystine is needed because cystine stones are difficult to noninvasively differentiate from more common calcium-containing ones. Tandem mass spectrometry (MS/MS) is sensitive and specific but is labor-intensive and costly. Alternatively, a colorimetric assay is fast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The standard sodium nitroprusside assay (Figure a) quantifies cystine solubility in urine samples. , During the study, it was found that as the pH increased from 5.5 to 7.5, cystine solubility in a healthy patient urine sample increased in the presence of both tiopronin and tiopronin-NO (Figure b–d). This indicates that thiol exchange occurs more quickly at pH 7.5 and reaches equilibrium at 48 h since alkali treatments break down cystine stones .…”
Section: Resultsmentioning
confidence: 99%
“…The standard sodium nitroprusside assay (Figure a) quantifies cystine solubility in urine samples. , During the study, it was found that as the pH increased from 5.5 to 7.5, cystine solubility in a healthy patient urine sample increased in the presence of both tiopronin and tiopronin-NO (Figure b–d). This indicates that thiol exchange occurs more quickly at pH 7.5 and reaches equilibrium at 48 h since alkali treatments break down cystine stones .…”
Section: Resultsmentioning
confidence: 99%